Enhancing Food Security and Alleviating Poverty: Community Responses to the Poor Rice Program in Jaranguda Village, Indonesia - Simbolon, Roma Sinta; Shylendra, Finan (Institute for Law and Economics Studies, 2022)
This study evaluates the impact of the Poor Rice Program in Jaranguda Village, located in the Merdeka District of the Karo Regency, Indonesia. The research employs a mixed-method approach, combining quantitative and qualitative analyses to comprehensively assess the program's effectiveness in addressing food insecurity, reducing household expenses, and engaging the community. Quantitative analysis of household surveys revealed a substantial reduction, averaging 30%, in monthly food expenses among program beneficiaries. Moreover, the provision of subsidized or free rice significantly decreased reported food insecurity incidents by 40%, ensuring a more stable and consistent food supply. Qualitative data from community feedback highlighted a strong sense of appreciation for the program's assistance, along with suggestions for improved distribution mechanisms and increased community engagement. These insights emphasize the need for ongoing dialogue and program adaptability to better cater to the evolving needs of the community. The findings underscore the significant impact of the Poor Rice Program in alleviating financial burdens and improving food security within Jaranguda Village. The reduction in household expenses and enhanced food security among beneficiaries signify the tangible outcomes of targeted interventions, emphasizing the importance of responsive, community-driven programs in addressing poverty-related challenges. This research contributes empirical evidence supporting the effectiveness of poverty-alleviation initiatives, providing valuable insights for policy development and future interventions in similar contexts. The findings offer a foundation for guiding community-driven programs aimed at improving the well-being of vulnerable populations.